Perceived Collective Continuity: Scale Adaption for the Russian Context - Terskova, M.A.; Bogatyreva, N.I.; Ivanov, A.A.; Romanova, M.O.; Bykov, A.O.; Ankushev, V.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2022)
This article presents the results of the adaptation of the scale for perceived collective continuity in Russian, the construct of which was initially developed by Sani and colleagues in 2007. The phenomenon of perceived collective continuity reflects the perception of groups as entities that are stable over time and transmit traditions from generation to generation. The perception of collective continuity is based on two main dimensions: perceived cultural continuity (perceived continuity of norms and traditions) and perceived historical continuity (perceived relationship between different historical eras and events). Six hundred thirty-seven Russians took part in testing the methodology. The methodology fit well the empirical data, highlighting the two-factor structure of the construct and validity of its scale. In general, the method of perceived collective continuity demonstrates good psychometric indicators and can be used for research in the field of intergroup relations as a reliable and stable toolkit. В статье представлены результаты адаптации шкалы воспринимаемой коллективной преемственности на русский язык, конструкт которой был изначально разработан Ф. Сани и коллегами в 2007 г. Феномен воспринимаемой коллективной преемственности отражает восприятие групп как сущностей, устойчивых во времени и передающих традиции из поколения в поколение. Восприятие коллективной преемственности основано на двух основных измерениях: воспринимаемой культурной преемственности (воспринимаемой непрерывности норм и традиций) и воспринимаемой исторической преемственности (воспринимаемой взаимосвязи между разными историческими эпохами и событиями). В апробации методики приняли участие 637 жителей России. Методика продемонстрировала хорошее соответствие эмпирическим данным, обозначив двухфакторную структуру конструкта и валидность шкалы. В целом, методика воспринимаемой коллективной преемственности демонстрирует хорошие психометрические показатели и может быть использована для исследований в области межгрупповых отношений как надежный и устойчивый инструментарий.